DEVELOPMENT OF STANDARD OPERATING PROCEDURES (SOP) FOR MARKETING SERVICES IN AN EFFORT TO IMPROVE THE SERVICE QUALITY OF PROSPECTIVE PILGRIMS AT PT RAJA UMROH BERKAH (POLITEKNIK LP3I JAKARTA, 2026)
This research was conducted to determine marketing services in an effort to improve the quality of services for prospective pilgrims at PT Raja Umroh Berkah. The purpose of this research is to determine the service procedures, obstacles, and solutions in the preparation of Standard Operating Procedures (SOP) at PT Raja Umroh Berkah. Data collection techniques were carried out through observation, namely by directly observing the object being studied. The obstacles that occurred in Marketing Services at PT Raja Umroh Berkah were the absence of a written SOP regulating a standard workflow, internal coordination problems between the administration and marketing departments, and a lack of consistency in the follow-up process for prospective pilgrims’ data. The solution carried out to overcome these obstacles was to prepare a structured Marketing Service SOP design, which included three main stages: the initial data reception process, technical coordination between divisions, and follow-up communication with prospective pilgrims. The method used to raise awareness of the importance of correct procedures was to implement this SOP as an official company guideline so that marketing staff could provide consistent, responsive, and professional services in order to increase the satisfaction of prospective pilgrims.